Penentuan Kandungan Fluorida Total dalam Air Minum dan Pasta Gigi Menggunakan Potensiometri dengan Ion Selektif Elektroda - Wahyuni, Sri; Nandini, Kinanti Sasura; Suherman, Alex L. (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2025)
This study determined fluoride levels in bottled drinking water and toothpaste using a fluoride ion-selective electrode (F-ISE) and verified the results using a colorimetric method based on alizarin complexone with UV–Vis spectrophotometry. F-ISE calibration with NaF standards (0.01–1.0 mg/L) in TISAB (1:1) showed excellent linearity (R² = 0.9996) and near-Nernstian response, with an average recovery of 88.2%. Most bottled water samples contained fluoride below the safety limit, except one brand (IND) with 2.289 mg/L, exceeding the WHO guideline (1.5 mg/L). Among toothpaste samples, one adult formulation (PEP) met BPOM standards, two children’s products (KOD and ENZ) were within safe ranges, while another adult product (CAL) exceeded the recommended fluoride level. Cross-validation on four representative samples showed good linearity for the colorimetric method (R² = 0.998) and inter-method deviations below 4%, indicating strong agreement between the two analytical approaches. The effect of Al³⁺ and Fe³⁺ interference on F-ISE measurements was also assessed. Without TISAB, fluoride readings decreased by 18–28% due to complex formation, whereas TISAB addition effectively minimized interference, leaving a residual bias of 1.7–4.4%.